THE ROLE OF ARTIFICIAL INTELLIGENCE IN SHAPING THE FUTURE OF CREATIVE WRITING AND LITERATURE (American Journal of Research in Humanities and Social Sciences, 2025)
This paper explores the impact of artificial intelligence (AI) on literature and human intellect. It highlights the positive contributions of AI in improving accessibility, translation, writing, and literary analysis. However, it also addresses concerns about the diminishing of human creativity, emotional connection, reading habits, and critical thinking. The paper examines how AI’s influence may affect the transmission of cultural heritage and intellectual engagement. Ultimately, it stresses the importance of finding a balance between leveraging AI’s advantages and preserving human qualities in literature and intellectual pursuits.